An assessment of the perceptual role of individual acoustic (infant cry): article / Muhammad Hafiz Abdullah @ Gerugu Randi - Abdullah @ Gerugu Randi, Muhammad Hafiz (2009)
This paper presents the build up of feature extraction for infant cry, with the objective to find new algorithm for three types of infant with three types of cry: normal and operate infant born with less risk to having disease and also normal infant born with potential to having serious illness. Linear prediction cepstral coefficient technique is used to obtain acoustic characteristics. The results show that we can extract the information from infants cry signal to produce a characteristic for feature extraction.